The Influence Of Plastic Wrap Types On Oxygen Detection Property By Colorimetric Oxygen Indicator Based On TiO2/Methylene Blue Nanocomposite - Natchapon Rattanaanothaikul; Parituch Lattanand; Maneerat Songpanit; Sutee Chutipaijit; Wanichaya Mekprasart (Thai Journal of Nanoscience and Nanotechnology, 2023)
The work is focused on the oxygen detection of colorimetric oxygen indicators by covering the indicator surface with different plastic wrap types. The layer of colorimetric detection was composed of titanium dioxides nanoparticles (TiO2), citric acid, methylene blue (MB) and polyvinyl alcohol (PVA). The precursor suspension was operated at 250 rpm by dry and wet milling process for 30 and 45 min. After that TiO2/MB composite was coated by the spin coating technique with a spin speed of 3000 rpm and 5 film layers on a glass substrate. The oxygen indicator with TiO2/MB composite film was presented in a blue film as indicated initial state. Then, plastic wraps with different types as polyvinylidene chloride (PVDC), polyvinyl chloride (PVC) and polyethylene (PE) were covered on the indicator surface to monitor its physical morphology, optical properties, and oxygen detection. Color changing in bleach and color state and oxygen detection of the indicators with the different plastic wraps were monitored by the snapshots in each hour for the cyan percentage analysis in the CMYK system. Meanwhile, the presence of bleach/color state in the indicators was confirmed by UV-Vis spectrophotometer focusing on the absorption range of MB dye to identify its state. The optimized covering plastic wrap on TiO2/MB colorimetric indicator was obtained by polyvinyl chloride that showed the identical indicator efficiency compared with the original indicator without the plastic wrap owing to good oxygen gas flow on its membrane. While the retardation of color changing in the indicator occurred by the polyethylene wrap on its surface due to the unique property of blocking oxygen gas flow.
Keywords: Analytical Chemistry and Sensors; Water Quality Monitoring and Analysis; Electrochemical sensors and biosensors